If x + y = 6, then solve for y to get: y = 6 - x.
Now replace y with 6 - x in both equations.
(5x)/3 + 6 - x = c
2(6 - x) = c - 4x
The upper equation is solved for c.
Now we solve the lower equation for c.
c = 2(6 - x) + 4x
c = 12 - 2x + 4x
c = 2x + 12
Since we have two equations solved for c, we substitute to get
(5x)/3 + 6 - x = 2x + 12
This is an equation in only x, so we can solve for x.
(5x)/3 - 3x = 6
5x - 9x = 18
-4x = 18
x = -9/2
Now we solve for y.
x + y = 6
-9/2 + y = 6
y = 9/2 + 12/2
y = 21/2
Now we solve for c.
c = (5x)/3 + y
c = (5 * (-9/2))/3 + 21/2
c = -45/6 + 21/2
c = -15/2 + 21/2
c = 6/2
c = 3
Answer: c = 3
C. Moved to a different location but congruent in size and shape.
Rigid motion transformations are when a shape is moved, rotated, reflected, or any other type of transformation but the size and shape stay the same.
Non-rigid is when an object is moved but the size and shape can change.
Hope this helps :))
Answer:
x= -2/9
Step-by-step explanation:
2(x-2)/5=4x
2(x-2)=4x*5
2(x-2)=20x
x-2=20x/2
x-2=10x
-2=10x-x
9x= -2
x= -2/9
Answer:
<u><em>B. 25</em></u>
Step-by-step explanation: